Customer Relationship Management in the world of e-commerce - Kaur , Surinder (Gyan Management Journal, 2016)
The latest paradigm in the world of Customer Relationship Management is e-CRM or Electronic Customer Relationship Management. E-CRM is a business strategy that utilizes the latest technological developments to tie together all aspects of a company's business with the goal of building long-term customer loyalty. Practically it can be described as the management of customer interactions at all levels, channels, and media. The web-enabled companies are no longer relying on the traditional brick & mortar strategies in order to ensure their stability in the global market. Implementation of an E-CRM system enables an organization to streamline processes and provide sales, marketing and service personnel with better, more complete customer information. The objective of this paper is to analyse the best CRM solutions available to the business organisations and the probable causes of more and more businesses moving towards accepting E-CRM as an important business strategy. The data for the purpose of this study is collected from secondary sources.
Keywords: Mailchimp; database; Oracle; Electronic Commerce